Competition and credit allocation in Kenya - Stephanie Kimani; Faith Atiti; Raphael Agung (Kenya Bankers Association (KBA), 2021)
Literature has divergent views on the relationship between market structure and allocation of credit by banks. Using quarterly bank scope data from 23 banks operating in Kenya between 2006 and 2018, we find that, while an increase in competition may improve allocation of credit in the short run, in the long run, increased competition may be detrimental to the amount of credit supplied to the private sector by commercial banks. This finding provides policy makers with evidence of how the structure of the Kenyan banking industry affects banks' credit allocation decisions. The findings may help inform the ongoing banking sector consolidation narrative given that changes to the competition structure of the market may not materially alter banks' lending behavior in the short and long run.
Keywords: 330; Kreditmarkt; Allokationseffizienz; Marktstruktur; Wettbewerbsanalyse; Kenia